On ice supersaturation over the Arctic - Gierens, Klaus Martin; Wilhelm, Lena; Sommer, Michael; Weaver, Dan (Meteorologische Zeitschrift, 2020)
We study ice-supersaturation in the cold (<-38°C) arctic troposphere and lower stratosphere using high-resolution quality-controlled radiosonde data. On average, ice supersaturation occurs in about 40 % to 60 % of the profiles with frequency of occurrence increasing with geographic latitude. The frequencies of occurrence show (so far) no long-term trends. The seasonal cycles are not very clear but seem to reverse between more southern to more northern locations. Most profiles with ice-supersaturation have more than one supersaturated layer; this stacking increases as well to the north. Due to the 1‑Hz resolution of the data we find ice-supersaturated layers a few metres thick, but very thick layers extending over almost 5 km are found as well. Median thickness values are smaller than in previous studies, between 100 m and 200 m. The far northern locations display a strong seasonal cycle of the mean layer thickness with maxima in the polar night, probably caused by radiation cooling. Ice supersaturation occurs most frequently directly beneath the tropopause in an upper-tropospheric layer whose depth varies strongly seasonally, being thin in summer and much thicker in winter. Due to the very low temperatures in the Arctic ice supersaturation can occur at the ground. Temperatures in arctic supersaturated layers typically range from -40 to -60 °C, but can occasionally be lower than -70 °C. Water vapour volume mixing ratios range from a few to about 500 ppmv. The relative humidity with respect to ice can exceed 150-160 %. The thickness of supersaturated layers is weakly correlated with its maximum supersaturation, but not with temperature and absolute humidity.